2018
DOI: 10.1680/jmacr.16.00495
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear flexural behaviour of RC columns including bar buckling and fatigue degradation

Abstract: An advanced fibre-based modelling technique is developed to characterise the nonlinear flexural behaviour of rectangular reinforced concrete (RC) columns by accounting for the influence of inelastic buckling and low-cycle fatigue degradation of vertical reinforcement. The proposed uniaxial material model of reinforcing steel is calibrated using 22 rectangular RC column tests. The influence of inelastic buckling of vertical reinforcement on the nonlinear cyclic response of rectangular RC columns is investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The improved fiber beam-column model employed in this study significantly increases the capabilities of RC structural modeling by capturing the inelastic buckling and low-cycle fatigue degradation of longitudinal reinforcing bars. Previously, Kashani et al [28][29][30][31] developed a modeling technique for RC columns. In this paper, the same modeling technique is employed for RC building frames.…”
Section: Finite Element Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved fiber beam-column model employed in this study significantly increases the capabilities of RC structural modeling by capturing the inelastic buckling and low-cycle fatigue degradation of longitudinal reinforcing bars. Previously, Kashani et al [28][29][30][31] developed a modeling technique for RC columns. In this paper, the same modeling technique is employed for RC building frames.…”
Section: Finite Element Model Developmentmentioning
confidence: 99%
“…It has a parabolic curve up to the maximum concrete stress and a linear post-peak softening branch afterward. In another study [31] by the authors of this paper, it was found that After generating the FE model for the 2-story RC building, an eigenvalue analysis is performed after the gravity load analysis to compute the natural period of vibration of the structure, T1 (T1=0.5s). The computed T1 of the proposed model in this paper is slightly less than T1=0.6s reported by Haselton [24] using the lumped plasticity model.…”
Section: Uniaxial Materials Modelsmentioning
confidence: 99%
“…The numbers of fibers and the section discretization method are based on the recommendations provided by Berry and Eberhard [Berry and Eberhard] (2006). For more information regarding the methodology, formulation, calibration and validation of the model please refer to Kashani et al [Kashani, Salami, Goda et al (2017); Salami, Kashani and Goda (2019)]. Validated against experimental results, this computational modeling technique is capable to account for cyclic degradation of reinforcing bars due to inelastic buckling and low-cycle fatigue failure.…”
Section: Reinforced Concrete Modelmentioning
confidence: 99%
“…The model accounts for inelastic buckling and low-cycle fatigue degradation of longitudinal reinforcement and can simulate multiple failure modes of reinforced concrete structures under dynamic loading. A comprehensive detail of the model is available at Kashani et al [Kashani, Salami, Goda et al (2017); Dizaj, Madandoust and Kashani (2018); Salami, Kasani and Goda (2019)]. In addition to the advanced structural modeling, a comprehensive ground motion selection accounting for shallow crustal is implemented, as the hypothetical column is assumed to be located in Los Angeles, US.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated cyclic deformations frequently cause a deterioration of the characteristics of reinforced concrete (RC) mechanical systems. In fact, building structures may experience opening and closing of cracks, post-yielding and buckling of metallic elements (Kashani, Salami, Goda, & Alexander, 2018), strength and stiffness deterioration, and other local inelastic behaviours (Sivaselvan & Reinhorn, 2000). All these phenomena contribute to the structural damage.…”
Section: Introductionmentioning
confidence: 99%